2021
DOI: 10.2147/ppa.s303208
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Bilateral Risk-Reducing Mastectomy and Simultaneous Reconstruction Using Pre-Pectoral Silicone Implants

Abstract: Purpose Bilateral risk-reducing mastectomy (BRRM) can reduce the risk of developing breast cancer by up to 95% in women with increased exposure. Although survival is increased, mastectomies can adversely affect a patient physically, psychologically, and psychosexually. High health-related quality of life (HRQoL) is often achieved after simultaneous breast reconstruction (BR) following BRRM; however, data on the pre- and postoperative results of HRQoL are lacking. Therefore, we investigated the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…There are a dearth of studies examining use of prepectoral implants for reconstruction after BRRM. Two studies have reported high levels of patient satisfaction and low complication rates [ 34 , 35 ]. This upwards trend in use of prepectoral reconstruction is likely to continue for two important reasons.…”
Section: Discussionmentioning
confidence: 99%
“…There are a dearth of studies examining use of prepectoral implants for reconstruction after BRRM. Two studies have reported high levels of patient satisfaction and low complication rates [ 34 , 35 ]. This upwards trend in use of prepectoral reconstruction is likely to continue for two important reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to assess long-term nipple symmetry and satisfaction in women who undergo risk-reducing mastectomy in pre-pectoral breast reconstruction. Early small cohort data are promising [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…No studies reported EQ-5D outcomes in patients following RRM or RRSO. Four observational studies [41][42][43][44] reported on quality of life after RRM using SF-36. Summary scores (PCS-36 and MCS-36) were available in one study [43], whereas the other three studies reported dimension scores only, and hence, the summary scores were calculated [41,42,44].…”
Section: Included Studiesmentioning
confidence: 99%